Rental housing assetization through property management: the role of platforms real estate in Brazil - Batista, Lucas Meirelles Toledo Ramos (Geografares, 2026)
The consolidation of rental housing as a new asset class in core capitalist countries is rooted in the massive privatization of housing stock from social welfare programs and the loss of property due to mortgage defaults after the 2008 crisis. In contrast to the Brazilian scenario, this article argues that the absence of these conditions has required the adoption of alternative instruments to address the fragmented private market with multiple owners. Through the analysis of new products offered by platforms, the paper shows how these platforms have influenced the transformation of rental contracts and the flow of rents into capitalized property titles, deepening the financial logic and the hierarchization of space, thus strengthening the Wealth Management Industry.
Keywords: platforms real estate; rental housing; assetization